2017
DOI: 10.1371/journal.pone.0185487
|View full text |Cite
|
Sign up to set email alerts
|

The fine-scale genetic structure and evolution of the Japanese population

Abstract: The contemporary Japanese populations largely consist of three genetically distinct groups—Hondo, Ryukyu and Ainu. By principal-component analysis, while the three groups can be clearly separated, the Hondo people, comprising 99% of the Japanese, form one almost indistinguishable cluster. To understand fine-scale genetic structure, we applied powerful haplotype-based statistical methods to genome-wide single nucleotide polymorphism data from 1600 Japanese individuals, sampled from eight distinct regions in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 59 publications
4
26
0
Order By: Relevance
“…The distribution of the individuals projected onto the two-dimensional space by PCA largely reflected the geographic distribution. The PC1 corresponded to the northeast-tosouthwest geographic axis, which separated the Japanese population into two major clusters, as reported previously 16,20 . The "Hondo" cluster consisted mainly of the residents of the mainland (the four major Japanese islands, which included six regions in this study [i.e., Hokkaido, Tohoku, Kanto-Koshinetsu, Chubu-Hokuriku, Kinki, and Kyushu]; Supplementary Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The distribution of the individuals projected onto the two-dimensional space by PCA largely reflected the geographic distribution. The PC1 corresponded to the northeast-tosouthwest geographic axis, which separated the Japanese population into two major clusters, as reported previously 16,20 . The "Hondo" cluster consisted mainly of the residents of the mainland (the four major Japanese islands, which included six regions in this study [i.e., Hokkaido, Tohoku, Kanto-Koshinetsu, Chubu-Hokuriku, Kinki, and Kyushu]; Supplementary Fig.…”
Section: Resultssupporting
confidence: 80%
“…Japan, located far east of Africa and Europe as one of the ends of the human journey, has experienced a unique demographic history. One hypothesis assumes that two waves of human migration into Japan occurred: one from Southeast Asia 40,000 years ago, followed by another from the Korean Peninsula 3000 years ago 15,16 . Few admixture events have taken place after these migratory waves, and the population has been kept isolated within the mainland and the surrounding thousands of small islands.…”
mentioning
confidence: 99%
“…It appears that within-country population structure occurs across the world 6,25 , and in this study is observed down to scales of less than 10km. Such strong, localised genetic drift predicts the existence of geographically localised rare mutations, including pathogenic ones.…”
Section: Discussionmentioning
confidence: 51%
“…Recent studies have showcased the power of leveraging shared haplotypes to uncover and characterise previously unrecognised fine-grained genetic structure within populations, yielding novel insights into the demographic composition and history of Britain and Ireland 47 , Finland 8 , Japan 9 , Italy 10 and Spain 11 . Haplotype sharing has also revealed genetic affinities between populations, enabling inference of historical admixture events using modern populations as proxies for ancestral admixing sources 12 .…”
mentioning
confidence: 99%